Human Rights of Prisoners in Japan - Yamashita, Kiyoshi (Victoria University of Wellington Law Review, 1999)
In this article the author provides a practitioner perspective on the human rights of prisoners in Japan, with particular reference to the treatment of persons detained pending trial, and to seminal decisions of the Japanese courts in a civil claim against the State for violating the rights of a prisoner to the protection of their human dignity.